The Relationship Between Local Food Intake and Body Mass Index (BMI) In Women Of Childbearing Age (WCA) - Tiara Salsabilla, Isnaini; Luluk; Muwakhidah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Women of reproductive age (WUS) are a group of women aged between 15 and 49 years. They are considered a vulnerable group. Women with poor or severe nutritional status can develop chronic energy deficiency syndrome (CED). The direct causes of CED are dietary patterns and infections. Indonesia, which has a diverse range of food sources, can be utilized effectively. Local food is a source of food available in a region. If utilized effectively, it will provide several benefits, including affordability and ease of access. Objective: This study aims to determine the relationship between local food intake and BMI in women of reproductive age (WUS). Method: This study design is analytic cross-sectional with a sample of 162 respondents. The inclusion criteria for this study were women aged 19-39 years, women who are not pregnant, women who are not on a specific diet, and those who are willing to be respondents. The exclusion criteria were women who withdrew before the study was completed. The analysis was conducted using the Spearman rank correlation test. Results: The results show that most respondents are aged 30-39 years (79%), the majority of respondents have a secondary education level (SMA) (52.5%), respondents are in the unemployed category (84.6%), and the highest income of respondents is in the <UMR category (69.8%), normal BMI 46.9%, obesity category BMI 32.7%, overweight category BMI 13.6% and wasting category 6.8%. Conclusion: In conclusion, there is a relationship between energy and carbohydrate intake with WUS BMI. Protein and fat intake with WUS BMI has no relationship. Suggestion: It is recommended that the measurement of nutritional status in WUS can be supplemented using LILA, so that the results are more accurate. Measurement of nutrient intake can use a more detailed method, such as Food Recall.in the wasting category was 6.8%. Conclusion: There is a relationship between energy and carbohydrate intake and BMI in WUS. There is no relationship between protein and fat intake and BMI in WUS.